Changes in Microbial Necromass Carbon in Soil Profiles of Grasslands with Different Stages of Restoration in a Karst Region - Xuefeng Wu; Heng Liu; Xiaolong Bai; Dongpeng Lv; Mingzhi Lv; Yurong Yang; Wangjun Li (Agronomy, 2025)
Ecological restoration has increasingly been employed to reverse land degradation and increase carbon (C) sink, especially in ecologically fragile karst areas. Microbial necromass carbon (MNC) constitutes a critical pool within soil organic carbon (SOC), contributing substantially to long-term C sequestration through mineral stabilization. However, its distribution patterns across soil profiles and grassland restoration stages in karst areas remain unclear. To address this knowledge gap, the contents of bacterial necromass C (BNC), fungal necromass C (FNC), and their contributions to SOC were estimated based on glucosamine and muramic acid contents across the soil profile (0–20 cm, 20–40 cm, 40–60 cm, 60–80 cm, and 80–100 cm) for four subalpine restoration stages (grazing enclosure for 5, 11, 17, and 25 years) in the karst region. Our findings demonstrated that both soil depth and grassland restoration stages effectively influenced the BNC and FNC contents. On average, the soil BNC, FNC, and total MNC at the depth of 80–100 cm reduced by 70.50%, 59.70%, and 62.18% compared with in topsoil (0–20 cm), respectively. However, the FNC/BNC ratio gradually increased with the increase in soil depth, which was 43.15% higher at 80–100 cm soil depth than in topsoil, suggesting that the accumulation efficiency of FNC was higher compared to BNC in the deep soil. The BNC, FNC, and MNC were positively correlated with the grassland restoration stage, while FNC/BNC ratio had a negative relationship with the restoration stage (R2 = 0.45, p < 0.001). FNC contributed significantly more to SOC (28.6–36.4%) compared to BNC (7.7–9.9%) at all soil depths, indicating that soil fungal necromass has an essential effect on SOC sequestration. The results of the random forest model and distance-based redundancy analysis identified that pH, soil water content, and dissolved organic carbon were the three most essential predictors for the contribution of MNC to SOC. Our study highlights the importance of microbial necromass to SOC accumulation, providing significant scientific implications for the C pool management during the restoration of degraded grasslands in karst regions.